Setting of a maximum residue level for cyantraniliprole in leeks. (22nd January 2018) - ,; Brancato, Alba; Brocca, Daniela; De Lentdecker, Chloe; Erdos, Zoltan; Ferreira, Lucien; Greco, Luna; Jarrah, Samira; Kardassi, Dimitra; Leuschner, Renata; Lythgo, Christopher; Medina, Paula; et al.
Abstract: In accordance with Article 53 of Regulation (EC) 1107/2009, the United Kingdom granted a 120‐day emergency authorisation for the use of cyantraniliprole in leek. In order to accommodate for the new use, the Agriculture & Horticulture Development Board submitted an application to raise the existing maximum residue level (MRL) for the crop concerned. The United Kingdom, as evaluating Member State, summarised the data provided by the applicant in an evaluation report which was submitted to the European Commission and forwarded to EFSA. Sufficient residue trials are available to derive an MRL proposal of 0.6 mg/kg for leeks in accordance with the emergency authorised good agricultural practice (GAP). Adequate analytical methods for enforcement are available to control the residues of cyantraniliprole in the commodities under consideration. Based on the risk assessment results, EFSA concluded that intake of residues resulting from the use of cyantraniliprole according to the reported agricultural practice is unlikely to present a risk to consumer health.